A sustainable multi-objective framework for designing and planning the supply chain of natural gas components. (20th June 2020) - Zarei, Javad; Amin-Naseri, Mohammad Reza; Fakehi Khorasani, Amir Hossein; Kashan, Ali Husseinzadeh
Abstract: Concerns about environmental and social issues have led international organizations to pressure companies to invest in sustainable development. Therefore, economic, environmental and social dimensions should be taken into account simultaneously in energy supply planning and policy making. Additionally, one of the world's major sources of energy is natural gas with valuable hydrocarbon components. Since the change in demand for one of these components and the consequent change in natural gas extraction affects the other components, integrated planning for the supply chain of these components is required. Accordingly, the purpose of this study is to design and plan an optimal and sustainable supply chain for natural gas components in order to maximize total profit and minimize both total greenhouse gas (GHG) emissions and total water consumption, as well as optimize strategic and tactical decisions. A multi-objective mixed integer linear programming (MOMILP) model is developed for this supply chain and converted to a single-objective model using the fuzzy programming approach. Finally, data provided from the Iranian gas industry is applied to solve the developed model and a sensitivity analysis is carried out to demonstrate the effect of important parameters on values of objective functions. The results indicate that condensate product sales revenue, as well as GHG emissions and water consumption in refineries, have the highest share in each objective function. Additionally, while refineries emit GHG more than transmission pipelines, changing the parameters of GHG emissions in pipelines has a much greater impact on total GHG emissions in the supply chain compared with refineries. Graphical abstract: Image 1 Highlights: A sustainable multi-objective framework for natural gas supply chain is proposed. Optimal design and planning of multi-product natural gas supply chain is performed. Refineries have the highest share of total GHG emissions and total water consumption. Change of GHG emissions in pipelines has the greatest impact on total GHG emissions.